Improvement Line Process to Reduce Production Cost Using Lean Six Sigma Approach (The Indonesian Journal of Business Administration, 2012)
According to the  multidmensional economic crisis  that impact on  increasing  drug  prices,  especially prices of patented drugs /  trademark, these  condition  affect  to  the  failure in fulfill  of public  health  due  to  decreasing  of purchase power. To cope these conditions required participation of the pharmaceutical industry   especially in   the manufacture   to develop   and   socialize affordable drugs by all segments of civil society.This project aims to reduce the unit cost of products and that will directly affect the COGS product. Performed incrementally by selecting  several  products  that provide  the  main  value  of PT. AAA. To analyze the   causes and    solutions    to the    problem, Six Sigma framework (DMAIC)  was used  which combined with the concept   of Lean Manufacturing to eliminate  non-value added processes called ―Lean Six Sigma". Lean Six Sigma is a methodology for improvement which can be used for all processes with the aim to achieve better conditions, faster, cheaper, and safer.Three products selected as pilot project for improvement of products. As-is condition indicates the number of waste were identified that affect the efficiency of the line process. The target of this improvement is to eliminate waste and improve line efficiency. From the results of root caused analysis, can  implemented general and   specific   solutions   for   the   three   products.   In   this   case, implementing 5S, work standardization, escalation system, autonomous maintenance, and vision performance system become the solutions.All solutions are implemented aimed to improve line efficiency and reduce man hours that could affect the cost reduction.Saving from this project in a year is IDR 226 million. Keywords:  Unit Cost, Lean Six Sigma,Six Sigma,Lean Manufacturing, DMAIC